2020
DOI: 10.1142/s0219455420300025
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Vibration Analysis of Functionally Graded Beams

Abstract: Beams and beam structures are structural components commonly used in mechanical, aerospace, nuclear, and civil engineering. To meet the different engineering design limitations such as operational conditions, weight, and vibrational characteristics, these components may be made of various materials such as functionally-graded materials (FGMs), composites, and homogeneous materials. Functionally-graded (FG) beams play a key role not only in classical structural applications, but also have vast applications in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 214 publications
0
4
0
Order By: Relevance
“…Özellikle malzeme fazları arasındaki yumuşak geçişleri tanımlamak amacıyla tercih edilir. Matematiksel olarak sigmoid fonksiyon, aşağıdaki formülle ifade edilir [39]:…”
Section: B Dağılım Modelleriunclassified
“…Özellikle malzeme fazları arasındaki yumuşak geçişleri tanımlamak amacıyla tercih edilir. Matematiksel olarak sigmoid fonksiyon, aşağıdaki formülle ifade edilir [39]:…”
Section: B Dağılım Modelleriunclassified
“…Cheng et al (2011) studied free vibration analysis of cracked rotating tapered beams using P-version FEM. Zahedinejad et al (2020) provided a complete review on vibration of FGM beams. Vibrational analysis of pre-twisted FGM tapered beams is done using Rayleigh–Ritz along with Kane’s method by Oh and Yoo (2016).…”
Section: Introductionmentioning
confidence: 99%
“…The FGMs are normally made from isotropic materials (metals and ceramics) and have remarkable properties such as high strength, low weight, long fatigue life and wear resistance. Therefore, these materials have extensively been used in different applications, and hence, various analyses (static, dynamics…) on the behaviour of structures made of FGMs have been carried out (Cong et al, 2018; Jin et al, 2019; Khaneh Masjedi et al, 2019; Lee and Lee, 2017; Pradhan and Chakraverty, 2013; Sarkar and Ganguli, 2014; Zahedinejad et al, 2020). The dynamic behaviour of FGM structures is an active research area and has attracted the interest of many researchers (Amoozgar et al, 2017; Giunta et al, 2011; Lü et al, 2008; Şimşek and Kocatürk, 2009; Sina et al, 2009; Vo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The quasi-3D dynamic behaviour of functionally graded beams using Carrera unified beam formulation was studied by Jin et al (2019). Zahedinejad et al (2020) presented a comprehensive literature review of the research studies carried out on the vibration of FGM beams. More recently, Tian et al (2019) studied the effect of porosity and material grading on the fundamental frequencies of rotating FGM beams and showed that the rotational speed, hub radius and porosity affect the dynamics of the beam significantly.…”
Section: Introductionmentioning
confidence: 99%